Synthesis of gadolinium oxide nanocuboids for in vitro bioimaging applications. (13th September 2019) - Chawda, Nitya; Mishra, Sarthak; Basu, Mainak; Chander, Harish; Podder, Raju; Mahapatra, S K; Banerjee, I
Abstract: Undoped and Eu-doped gadolinium oxide (GGNCs and EGNCs) nanocuboids functionalized with D-gluconic acid (GA) were synthesised by a simple yet unique scheme using all the benign solvents and temperature. Samples were characterized and presented with properties like good dispersity, biocompatibility, and stability required for standard contrast agent used in magnetic resonance imaging (MRI) and optical coherence tomography (OCT). Biological assays such as 3-(4, 5-dimethyl-2-yl)-2, 5-diphenyltetrazoliumbromide (MTT) assay, flow cytometry and confocal microscopy were used to determine its biocompatibility, cellular internalization and optical cellular imaging using A549 and H1299 lung cancer cell lines. EGNCs treated with cell lines emitted red fluorescence which was used to track the internalization of EGNCs within the cells. GGNCs sample showed ∼20% enhanced MRI relaxivity as compared to EGNCs; whereas EGNCs revealed better contrast in doctor scans of OCT. Samples could be used as promising candidate for other biomedical applications such as drug delivery when equipped with well functionalised drug molecules.